2013
DOI: 10.1080/21663831.2013.804218
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of bcc Mg in Thin Films at Ambient Pressure: Experimental Evidence andab initioCalculations

Abstract: Recent experiments suggest that bcc Mg can be stabilized when grown together with bcc Nb in Mg/Nb multilayer films at ambient conditions. This finding is remarkable as (pure) bcc Mg has only been observed under very high pressures and is in fact (mechanically) unstable under room conditions. Density functional theory calculations were performed to gain insight into the stability of Mg in the bcc structure. Calculations of the thermodynamic, electronic and structural stability of bcc Mg show that this structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
(35 reference statements)
1
15
2
Order By: Relevance
“…These textures are consistent with prior microstructural analyses of fully BCC Mg/Nb composites. 42,46,47 In other studies, however, the 5 nm/5 nm Mg/Nb composite was not fully BCC. Instead, there, finer h to 2.5 nm (with Nb at the same h) or 1.5 nm (with Nb at a smaller h) was needed to create the fully BCC Mg/BCC Nb composite.…”
Section: Interface-induced Phase Transformationmentioning
confidence: 82%
“…These textures are consistent with prior microstructural analyses of fully BCC Mg/Nb composites. 42,46,47 In other studies, however, the 5 nm/5 nm Mg/Nb composite was not fully BCC. Instead, there, finer h to 2.5 nm (with Nb at the same h) or 1.5 nm (with Nb at a smaller h) was needed to create the fully BCC Mg/BCC Nb composite.…”
Section: Interface-induced Phase Transformationmentioning
confidence: 82%
“…The calculation results based on first-principles theory from Jona and Marcus revealed a martensitic transition of Mg from HCP structure to BCC structure at hydrostatic pressure lager than 500 kbar [35]. Moreover, the metastable BCC Mg were experimentally observed in the magnetron sputtered Mg/Nb multilayers with individual layer thickness of 5 nm, while subsequent density functional theory calculations demonstrated that the stabilization of BCC Mg deposited on BCC Nb substrate is analogous to the stabilization of BCC Mg under high pressures because of the mechanical constraints imposed on Mg [36,37].…”
Section: Microstructural Stabilitymentioning
confidence: 93%
“…Thus bulk Nb exists in bcc form. Meanwhile bcc Mg can form under high pressure, since compression can stabilize the bcc Mg structure by lowering of its 3d band toward the Fermi level (E F ) [55,56,21].…”
Section: (A) and (B) Show Electron Distribution Directions And Interamentioning
confidence: 99%
“…The charge density and ELF contour of the unit cell were visualized by using VESTA [45]. [30,21]. Coherent interfaces with bcc structure were observed in Mg 5.6 nm/Nb 10.4 nm multilayers ( Fig.…”
Section: ½2mentioning
confidence: 99%
See 1 more Smart Citation